Peroxiredoxin 2 expression is increased in neutrophils of patients with refractory cytopenia with multilineage dysplasia. (26th May 2014) - Kazama, Hiroshi; Teramura, Masanao; Kurihara, Sachiko; Yoshinaga, Kentaro; Kato, Tomohiro; Motoji, Toshiko
Summary Myelodysplastic syndromes (MDS) are heterogeneous clonal disorders characterized by cytopenias that arise due to ineffective haematopoiesis and morphological dysplasia and carry an increased risk of incident acute myeloid leukaemia. The pathogenesis of marrow dysfunction in MDS is multifactorial and consistent with a multistep model and may lead to heterogeneity of MDS. We investigated the proteome profile of circulating neutrophils purified from patients with refractory cytopenia with multilineage dysplasia (RCMD) to identify proteins that have a role in the pathogenesis. Using 2‐dimensional difference gel electrophoresis and protein identification by matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry, we found that peroxiredoxin 2 (PRDX2), a member of the peroxiredoxin family that regulates reactive oxygen species, was markedly upregulated in neutrophils of RCMD patients compared to healthy donors. Increased PRDX2 expression in the neutrophils of RCMD patients was confirmed using quantitative reverse transcription polymerase chain reaction, immunoblotting and immunocytochemical analysis. In addition, white blood cell and neutrophil counts in RCMD patients correlated inversely with the PRDX2 expression of. Oxidative stress is a known factor involved in the pathogenesis of MDS, and PRDX2 is associated with tumourigenesis of several solid tumours. Accordingly, our results suggest that PRDX2 may perform an important function in the pathogeneis of RCMD.